State-of-art review of bacteria-based self-healing concrete: Biomineralization process, crack healing, and mechanical properties. (16th May 2023) - Aytekin, Burcu; Mardani, Ali; Yazıcı, Şemsi
Highlights: Bacterial impact on concrete's characteristics. Concrete can develop calcium carbonate precipitation due to bacteria. Concrete that uses microorganism-based self-healing can be improved over time. Environmental variables (temperature, pH etc.) can affect the microbial viability of concrete. Implementation of encapsulation strategies has been proposed to enhance self-healing capabilities. Abstract: Concrete, one of the most important building materials, has been in use for nearly two hundred years and will likely continue to be the dominant building material for the foreseeable future. Therefore, its role in the world economy is crucial. However, cracks are almost inevitable in fresh and hardened concrete due to load-independent or load-related reasons. Furthermore, it is often difficult to detect and repair these cracks and pose a threat to the safety and durability of concrete infrastructures, especially in those with stringent sealing requirements. Therefore, bacteria-based remediation using microorganisms is a promising solution for both repairing cracks without manual intervention and sustainable concrete maintenance. In this respect, in this study, the effects of parameters such as biomineralization processes and environmental conditions, bacterial species, type of inclusion in the system, nutrient medium, crack width, microbiological and durability properties of bacterial concrete on microbial self-healing performance are discussed in detail.